Ghrelin response to acute and chronic exercise: insights and implications from a systematic review of the literature - Ouerghi, N.; Feki, M.; Bragazzi, N. L.; Knechtle, B.; Hill, L.; Nikolaidis, P. T.; Bouassida, A. (Sports Medicine, 2021)
Background: Ghrelin is a peptide hormone predominantly produced by the stomach. It exerts a wide range of functions including stimulating growth hormone release and regulating appetite, food intake, and glucose and lipid metabolism. Since physical exercise affects all these aspects, a particular interest is accorded to the relationship between ghrelin and exercise. This systematic review aimed to summarize the current available data on the topic for a better understanding of the relationship. Methods: An extensive computerized search was performed in the PubMed and SPORTDiscus databases for retrieving relevant articles. The search contained the following keywords: ghrelin, appetite-related peptides, gastrointestinal peptides, gastrointestinal hormones, exercise, acute exercise, chronic exercise, training, and physical activity. Studies investigating the effects of acute/chronic exercise on circulating forms of ghrelin were included. Results: The initial search identified 840 articles. After screening, 80 articles were included. Despite a heterogeneity of studies and a variability of the findings, the review suggests that acute exercise suppresses acyl ghrelin production regardless of the participants and the exercise characteristics. Long- and very long-term exercise training programs mostly resulted in increased total and des-acyl ghrelin production. The increase is more noticeable in overweight/obese individuals, and is most likely due to weight loss resulting from the training program. Conclusion: The review suggests that exercise may impact ghrelin production. While the precise mechanisms are unclear, the effects are likely due to blood flow redistribution and weight loss for acute and chronic exercise, respectively. These changes are expected to be metabolically beneficial. Further research is needed for a better understanding of the relationship between ghrelin and exercise.